Perancangan Sistem Informasi Stok Obat pada Apotek X Berbasis Web Menggunakan Metode Incremental - Michael Hadi Harto Wijaya; Fahrezi Egy Firmansyah; Nugroho Bintang Jaya Saputra (CV. Multi Kreasi Media, 2026)
The development of information technology in the pharmaceutical sector has increased the need for systems that can manage drug inventory efficiently and accurately. This study develops a web-based drug inventory information system at Pharmacy X using the incremental development method. This approach allows the system to be developed gradually, starting from basic modules to more advanced functionalities. The incremental method is chosen to reduce development risks, improve system quality, and provide usable features from the early stages of development. System evaluation is conducted through functional testing at each increment and by measuring user satisfaction with the implemented features.